Quasinormal modes of near extremal black branes - Starinets, A (2002)
We find quasinormal modes of near extremal black branes by solving a singular boundary value problem for the Heun equation. The corresponding eigenvalues determine the dispersion law for the collective excitations in the dual strongly coupled N=4 supersymmetric Yang-Mills theory at finite temperature. © 2002 The American Physical Society.